The Parkinson’s drug benztropine possesses histamine receptor 1-dependent host-directed antimicrobial activity against Mycobacterium tuberculosis - Henok A. Sahile; Matthew Christofferson; Morgan A. Alford; Celine Rens; Hasti Haghdadi; Joseph D. Chao; Georgia Langdon; Robert E. W. Hancock; Jeffrey Chen; Yossef Av-Gay (npj Antimicrobials and Resistance)
Abstract Intracellular pathogens such as Mycobacterium tuberculosis (Mtb) evade host defence mechanisms to infect and survive within host cells. Host-directed therapy (HDT) offers a promising alternative to antibiotics and may overcome antimicrobial resistance. Using high-content screening, we identified benztropine (BZT), an approved Parkinson’s disease drug, as a potent inhibitor of intracellular Mtb. BZT is active in both human and murine macrophages but is inactive in broth. In an aerosol Mtb mouse infection model, oral administration of BZT reduced the burden of Mtb in the lungs by up to 70%. BZT was also active against Salmonella enterica serovar Typhimurium (STm) in an abscess model of infection, significantly reducing size and bacterial load. Chemical competition assays, CRISPR knockouts, and siRNA silencing assays revealed that BZT’s activity against Mtb is mediated via macrophage histamine receptor 1 (HRH1). Our findings establish BZT as a promising repurposed candidate and a lead compound for developing HRH1-targeting antibacterial HDTs.